PENGARUH TATA KELOLA PERUSAHAAN, BIAYA AGENSI MANAJERIAL DAN LEVERAGE TERHADAP FINANCIAL DISTRESS - Intan Rimawati; Darsono Darsono (Diponegoro Journal of Accounting, 2017)
This study aims to obtain empirical evidence and to analyze the effect of corporate governance, managerial agency costs and leverage to financial distress.The  data  in  this  research  was  secondary  data  –  the  company’s  annual  reports.  The population of this study was manufacturing base and chemical industry sectors, the various sectors of the industry and the consumer goods industry sectors listed on the Indonesia Stock Exchange (IDX) in the year 2013-2015. This study use purposive sampling method to select sample from the population. Based on this method, at way obtained a sample of 303 companies comprising of 54 companies involved in financial distress and 249 companies that are not involved in financial distress. Data analysis was performed with descriptive statistics analysis and hypothesis testing by logistic regression analysis.The results of this study indicate that corporate governance negative and significant impact on the financial distress, while managerial agency costs and leverage positive and significant impact on the financial distress